Extraction of Essential Oil From Red Lettage (Andropogon Citratus DC) with Microwave Hydrodestillation Method - Yulia Vera; Hasni Yaturramadhan (Journal of Public Health and Pharmacy, 2021)
Essential oil derived from the red citronella plant (Andropogon Citratus DC) is usually used as fragrance and other ingredients. This study aims to study the extraction of essential oil from red lemongrass by hydrodistillation method with the help of microwave heating or known as microwave hydrodestillation. In the microwave hydrodestillation method, water is used as a solvent and using a conventional microwave with a power of 300 W and extraction time of 3 hours. The results of the study using the microwave hydrodestillation method obtained a yield of 0.5704%.